Pengembangan Lembar Kerja Peserta Didik Berbasis Model Problem Based Learning untuk Meningkatkan Hasil Belajar Kognitif dan Profil Karakter Gotong Royong pada Mata Pelajaran Pendidikan Pancasila di Sekolah Dasar - Awdiani, Dhea Putri; Juarsa, Osa; Widi Winarni, Endang (UNIB Press, 2025)
This research aims to develop a Student Worksheet (LKPD) based on the Problem-Based Learning (PBL) model to enhance cognitive learning outcomes and the cooperative character profile in Pancasila education subjects at the elementary school level. The type of research utilized is Research and Development (R&D) with the ADDIE development model, comprising five stages: analysis, design, development, implementation, and evaluation. The types of data used are quantitative and qualitative, with quantitative data derived from scoring questionnaires provided by validators, while qualitative data are critiques and suggestions from expert validation. Based on the research findings, the pretest and posttest scores indicated improvement, with the average pretest score of 57.2 and the average posttest score of 84.8. Additionally, the N-Gain Score test results revealed an average score of 76.60, categorized as high. Therefore, the LKPD based on the PBL model is suitable as teaching material to improve cognitive learning outcomes and cooperative character profiles, with the results showing appreciation at 93.74%, mutual assistance at 90.62%, and empathy at 92.84%.